Small Prey Animal Habitat Use in Landscapes of Fear: Effects of Predator Presence and Human Activity Along an Urban Disturbance Gradient - Fardell, Loren L.; Nano, Catherine E. M.; Pavey, Chris R.; Dickman, Christopher R. (Frontiers in Ecology and Evolution, 2021)
Human activity can impose additional stressors to wildlife, both directly and indirectly, including through the introduction of predators and influences on native predators. As urban and adjacent environments are becoming increasingly valuable habitat for wildlife, it is important to understand how susceptible taxa, like small prey animals, persist in urban environments under such additional stressors. Here, in order to determine how small prey animals’ foraging patterns change in response to habitat components and distances to predators and human disturbances, we used filmed giving-up density (GUD) trials under natural conditions along an urban disturbance gradient. We then ran further GUD trials with the addition of experimentally introduced stressors of: the odours of domestic cat (Felis catus)/red fox (Vulpes vulpes) as predator cues, light and sound as human disturbance cues, and their combinations. Small mammals were mostly observed foraging in the GUD trials, and to a lesser degree birds. Animals responded to proximity to predators and human disturbances when foraging under natural conditions, and used habitat components differently based on these distances. Along the urban disturbance gradient situation-specific responses were evident and differed under natural conditions compared to additional stressor conditions. The combined predator with human disturbance treatments resulted in responses of higher perceived risk at environments further from houses. Animals at the urban-edge environment foraged more across the whole site under the additional stressor conditions, but under natural conditions perceived less risk when foraging near predators and further from human disturbance (houses). Contrastingly, at the environments further from houses, foraging near human disturbance (paths/roads) when close to a predator was perceived as lower risk, but when foraging under introduced stressor conditions these disturbances were perceived as high risk. We propose that sensory and behavioural mechanisms, and stress exposure best explain our findings. Our results indicate that habitat components could be managed to reduce the impacts of high predation pressure and human activity in disturbed environments.